Prognostic impact of lymphadenectomy in uterine clear cell carcinoma - Mahdi, Haider (J Gynecol Oncol, 2015)
OBJECTIVE: The aim of this study was to estimate the survival impact of lymphadenectomy in patients diagnosed with uterine clear cell cancer (UCCC). METHODS: Patients with a diagnosis of UCCC were identified from Surveillance, Epidemiology, and End Results (SEER) program from 1988 to 2007. Only surgically treated patients were included. Statistical analysis using Student t-test, Kaplan-Meier survival methods, and Cox proportional hazard regression were performed. RESULTS: One thousand three hundred eighty-five patients met the inclusion criteria; 955 patients (68.9%) underwent lymphadenectomy. Older patients (≥65) were less likely to undergo lymphadenectomy compared with their younger cohorts (64.3% vs. 75.9%, p<0.001). The prevalence of nodal metastasis was 24.8%. Out of 724 women who had disease clinically confined to the uterus and underwent lymphadenectomy, 123 (17%) were found to have nodal metastasis. Lymphadenectomy was associated with improved survival. Patients who underwent lymphadenectomy were 39% (hazard ratio [HR], 0.61; 95% confidence interval [CI], 0.52 to 0.72; p<0.001) less likely to die than patient who did not have the procedure. Moreover, more extensive lymphadenectomy correlated positively with survival. Compared to patients with 0 nodes removed, patients with more extensive lymphadenectomy (1 to 10 and >10 nodes removed) were 32% (HR, 0.68; 95% CI, 0.56 to 0.83; p<0.001) and 47% (HR, 0.53; 95% CI, 0.43 to 0.65; p<0.001) less likely to die, respectively. CONCLUSION: The extent of lymphadenectomy is associated with an improved survival of patients diagnosed with UCCC.